Ontoestetyka dźwięku i kultura słuchania. Dyskurs metateoretyczny sound studies - Lniak, Agnieszka (Zagadnienia Rodzajów Literackich, 2021)
The article presents a critical approach to the sound studies debate, concerning its metatheoretical aspects. The point of departure is a paper by Brian Kane that opens the first issue of “Sound Studies: An Interdisciplinary Journal”. Kane criticizes the ontoaesthetic perspective within the discipline. My aim is to introduce sound studies both as an interdisciplinary and transdisciplinary field of humanities, dominated by two — instead of one referred by Kane — research strategies: audio-antropological and onto-aesthetical. By focusing on the latter, where the works by Christoph Cox and Salomé Voegelin are situated, I want to propose a different, affective-materialistic approach to sound studies, based not on the opposition between signification and sound/vibration, but on the relationship between the Deleuzoguattarian machinic concepts and the musical avant-garde. Referring to excerpts from articles and manifestos by Luigi Russolo, Edgar Varèse, Pierre Schaeffer and Pauline Oliveros, I show that the machinic sound imagination once accompanied the historical avantgarde and neo-avant-garde movements. It is the key to break with the anti-post-structural approach in sound studies in favor of a more relational perspective. This perspective, within the onesthetic paradigm, would allow for the interpretation of sound machinery as elements of the machine system (aesthetic, social, cultural) in which sound operates.